Pengaruh Kualitas Produk, Kualitas Pelayanan dan Harga Terhadap Loyalitas Pelanggan di Toko Kopi Bersaudara - Zuhrotul Khanifatun Nisa; Asrul Bahar; Nugrahani Astuti; Andika Kuncoro Widagdo (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
This research aims to find out: (1) the influence of product quality on customer loyalty at a Toko Kopi Bersaudara, (2) the influence of service quality on customer loyalty at a Toko Kopi Bersaudara, (3) the effect of price perceptions of customer loyalty at a Toko Kopi Bersaudara, and (4) the influence of product quality, Service quality, and price perception of customer loyalty at a Toko Kopi Bersaudara. This research is a quantitative descriptive study with a customer population at a coffee shop. Samples taken as many as 100 people with the survey data collection method using a questionnaire as a research instrument. Data analysis in this study includes validity test, realiability test, multiple linear regression analysis, F test (simultaneous test), T test (partial test), and analysis of coefficient of determination (R²). From the results of this study indicate that the variable of the product, service quality, and price perceptions have a positive and significant influence on customer loyalty at a Toko Kopi Bersaudara. The results of the research obtained based on the F test are Fcount> Ftable (64,535> 3,090) and the value of the sig. 0,000 <0.05 so the product quality variable, customer quality and price perception simultaneously have a positive and significant effect on customer loyalty (Y) at a Toko Kopi Bersaudara. Service quality is the most dominant variable affect customer loyalty at the Toko Kopi Bersaudara.